Improvement of Water Production for Drinking and Economic Needs of Yerevan and Management of Electricity Costs - Sahakyan, Aram; Kelejyan, Hovhannes (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
To increase the efficiency of the water supply system intended for the drinking and household needs of the city of Yerevan, as well as reduce energy consumption for water production, one of the most important activities is the development and implementation of local changes in the distribution network, as well as the water supply system, which will create the opportunity to transfer to gravity supply of a significant part of the city network facilities. The task was set, using the existing water supply system, water supply network, and daily regulation reservoirs, to maximize the amount of water obtained from sources at higher elevations. To pump additional outlets from sources located at higher elevations, it became necessary to create a flexible water supply system that allowed relatively inexpensive water from high mountain sources to be pumped to low-lying areas of the city. As a result of the implemented improvement, controllability, and efficiency of water systems, the amount of pumped water has decreased from 215 million m3 per year to 60 million m3 (72%), or from about 50% of water production to 21% at present.